1999
DOI: 10.1007/bf02347284
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of gamma-irradiated LaFeO3 and YFeO3 orthoferrites

Abstract: In the present work, LaFeO 3 and YFeO 3 orthoferrites were carefully prepared using the solid state high temperature ceramic and sintering technique. On these two materials, numerous measurements were applied before and after ~t-absorbed dose (1.24 Mrad) namely, X-ray diffraction (XRD), DC-electrical conductivity, UV/Vis, IR, MOssbauer effect and EPR. Results obtained were explained, interpreted, and discussed in detail on the basis of lattice structure of the new perovskite investigated and the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Pure rare earth ferrites have no bands in the region 4000-1000 cm −1 and the characteristic bands appear only between 600 cm −1 and 250 cm −1 indicating the absence of any impurity. Our spectra display bands at 383, 400, 420, 450, 558, 623 cm −1 and agree with those reported in the literature for LaFeO 3 [44][45][46][47][48][49][50][51][52][53][54][55]. The spectra present an intense band at 558 cm −1 with a shoulder at 623 cm −1 .The frequency band at 558 cm −1 was assigned to the Fe-O asymmetric stretching vibration mode which involves internal motion of a change in Fe-O bond length, whereas the shoulder can be assigned to the symmetric stretching vibration of Fe-O-Fe bands of the BO 6 octahedra [46,47].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Pure rare earth ferrites have no bands in the region 4000-1000 cm −1 and the characteristic bands appear only between 600 cm −1 and 250 cm −1 indicating the absence of any impurity. Our spectra display bands at 383, 400, 420, 450, 558, 623 cm −1 and agree with those reported in the literature for LaFeO 3 [44][45][46][47][48][49][50][51][52][53][54][55]. The spectra present an intense band at 558 cm −1 with a shoulder at 623 cm −1 .The frequency band at 558 cm −1 was assigned to the Fe-O asymmetric stretching vibration mode which involves internal motion of a change in Fe-O bond length, whereas the shoulder can be assigned to the symmetric stretching vibration of Fe-O-Fe bands of the BO 6 octahedra [46,47].…”
Section: Resultssupporting
confidence: 93%
“…8. The spectra showed bands in the higher wavenumber region of 650-500 and 450-370 cm −1 arising from the stretching modes and deformation modes of the FeO 6 octahedra, respectively [44,45]. Pure rare earth ferrites have no bands in the region 4000-1000 cm −1 and the characteristic bands appear only between 600 cm −1 and 250 cm −1 indicating the absence of any impurity.…”
Section: Resultsmentioning
confidence: 95%
“…The spectrum of the series Au/Fe 2 O 3 exhibited a broad band with maximum at ca. 245 nm, which can be assigned to electronic transition of d-d type in the Fe 3+ ion and is ascribed to the E g fi T 2g transition [53,54]. For those samples that did not undergo further reactions, an absorption band at about 385 nm can be observed, which corresponds to oxidized states of gold in the form of Au + and Au n d+ [55].…”
Section: Co Oxidation On Au/fe 2 Omentioning
confidence: 97%
“…Research has revealed that this perovskite is thermodynamically unstable and impurity phases Fe 3 O 4 or Y 3 Fe 5 O 12 (Yttrium Iron Garnet -YIG) are often created during high-temperature synthesis. That makes the preparation of single-phased perovskite YFeO 3 a complex task [4,[8][9][10][11][12][13][14]. Numbers of reports are available on YFeO 3 synthesis like sol-gel, microwaveassisted, self-propagating combustion synthesis, solid state reaction, alkoxide method, sonochemical synthesis, pulsed laser deposition, combustion or hydrothermal techniques, precipitation method, thermal decomposition, solvothermal treatment, Pechini method etc.…”
Section: Introductionmentioning
confidence: 99%